The cost efficiency effects of involuntary bank mergers: evidence from the Malaysian banking industry - Ab. Rahim, R.; Md Nor, N.G.; Ramlee, S.; Ahmad, F. (2009)
Much of the merger and banking efficiency studies is centered on the market driven or voluntary merger. Thus , the uniqueness of Malaysian merger policy offers an interesting platform for this study to embark on. The merger in Malaysia is unique as all the domestic banks were enforced to merge by the government in year 1999 after years of persuasion with little success. This study attempts to quantify the impact of the involuntary merger on the cost efficiency gains over the 1990-2005 periods. Firstly, several tests have been performed to investigate whether it is best to envelope data with a common frontier of data envelopment analysis (DEA) or by separate frontiers. Secondly, this paper assesses the cost, allocative, technical, pure technical and scale efficiencies of Malaysian banking industry as the results of the merger.Thirdly, a set of environmental variables (size, economic growth, market concentration, risk and the government ownership) are regressed on each type of the cost efficiencies using the Tobit regression model approach. To overcome the problem of the inherent dependency of DEA efficiency scores in the regression analysis, a bootstrapping technique is applied. In general, the results suggest that the enforcement of the bank merger policy has resulted in an improvement of bank efficiency levels.